Multimodal diagnostic approach for identifying Actinomyces odontolyticus pneumonia: a case report and literature review - Ya Shen; Xiao-Yu Cao; Jing-Feng Shi; Zi-Xiao Cao; Xiao-Bao Teng; Ming-Feng Han (Frontiers in Medicine, 2025)
The emergence of next-generation sequencing (NGS) has significantly improved the detection rate of Actinomyces species in pulmonary actinomycosis (PA), a rare and diagnostically challenging infectious disease. Here, we report a case of an elderly patient with a history of pyoderma gangrenosum who presented with pulmonary infiltrates and was subsequently hospitalized. Both histopathological examination of tracheoscopic biopsy specimens and NGS analysis of bronchoalveolar lavage fluid (BALF) confirmed infection with Actinomyces odontolyticus (A. odontolyticus). The patient exhibited marked clinical and radiological improvement following a period of amoxicillin/clavulanic acid therapy. Additionally, we performed a retrospective analysis of 11 documented cases of A. odontolyticus-associated pneumonia reported between 1978 and 2025. These cases were primarily diagnosed through pathogen culture and histopathology, with most patients demonstrating favorable outcomes following timely intervention. The age distribution of the cohort ranged from 11 to 64 years, with cough, sputum production, and dyspnea being the predominant symptoms. Notably, chest imaging findings varied widely. We anticipate that these findings will enhance clinical awareness of PA, facilitating early detection, accurate diagnosis, and improved patient management. To our knowledge, this represents the first reported case of A. odontolyticus pneumonia diagnosed using a combined NGS and histopathology approach, as well as the largest case series published for this condition.